2015
DOI: 10.1021/acssuschemeng.5b00032
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial Electrospun Cellulose-Core Fluoropolymer-Shell Fibrous Membrane from Recycled Cigarette Filter as Separator for High Performance Lithium-Ion Battery

Abstract: TitleCoaxial electrospun cellulose-core fluoropolymer-shell fibrous membrane from recycled cigarette filter as separator for high performance lithium-ion battery Permalink https://escholarship.org/uc/item/9gc5x56wJournal ACS Sustainable Chemistry and Engineering, 3(5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(74 citation statements)
references
References 30 publications
0
71
0
2
Order By: Relevance
“…Commercial separator and PVDF‐HFP fiber are severely shrunk while the core‐sheath separator remains intact. Compared to commercial separator, it also shows lower interfacial resistance ∼98.5 Ω, higher ionic conductivity ∼6.16 mS/m, superior rate capability ∼138 mA‐h/g and cycling performance ∼75.4 % after 100 cycles …”
Section: Recent Results and Applicationsmentioning
confidence: 99%
“…Commercial separator and PVDF‐HFP fiber are severely shrunk while the core‐sheath separator remains intact. Compared to commercial separator, it also shows lower interfacial resistance ∼98.5 Ω, higher ionic conductivity ∼6.16 mS/m, superior rate capability ∼138 mA‐h/g and cycling performance ∼75.4 % after 100 cycles …”
Section: Recent Results and Applicationsmentioning
confidence: 99%
“…However, PVdF and PVdF-HFP separators also have their disadvantages, such as the inferior thermal stability and intrinsically hydrophobic character. Wei et al [105] prepared cellulose/PVdF-HFP membranes by coaxial electrospinning with superior thermal stability and a hydrophilic property. Other electrospun PVdF-based materials, such as P(VdF-HFP)/SiO 2 [106,107], PVdF-HFP/PMMA [108], P(VdF-co-HFP)/PAN [109] and PVdF/SiO 2 -Poly(acrylic acid) lithium (PAALi) [110] as separators for LIBs, all delivered high ionic conductivity, good tensile strength and high uptake/leakage.…”
Section: Applicationsmentioning
confidence: 99%
“…It is reported that up to 5.6 trillion cigarette butts are disposed around the world each year, which is a significant threat to the environment (Figure a) . Previous works have focused on utilization of these disposed cigarette filters by carbonization or electrospinning technique . For example, Wei and coworkers used the cigarette filters to construct a cellulose‐based membrane by coaxial electrospinning for lithium‐ion battery .…”
Section: Introductionmentioning
confidence: 99%
“…[26] Previous works have focusedo nu tilization of these disposedc igarette filters by carbonization or electrospinning technique. [26][27][28][29] For example, Wei and coworkers used the cigarette filters to construct ac ellulose-based membrane by coaxiale lectrospinning for lithiumion battery. [27] Lee et al reported the synthesis of an itrogendoped porousc arbon material as as upercapacitor electrode from used cigarettef ilters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation